1994
DOI: 10.1227/00006123-199410000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Magnetic Resonance Angiography for Targeting in Arteriovenous Malformation Radiosurgery

Abstract: Because conventional stereotactic angiography provides only two-dimensional information for dose planning, we studied the accuracy and usefulness of stereotactic magnetic resonance angiography (sMRA) for arteriovenous malformation (AVM) radiosurgery in 28 consecutive patients. We hypothesized that the multidimensional data set provided by sMRA and the opportunity to image both blood vessels and brain parenchyma would improve the accuracy of AVM irradiation and improve the safety of radiosurgery. Twenty-eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…From the beginning of our AVM practice, dose planning was based on a combination of stereotactic biplanar angiography and either contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) to more effectively exclude the adjacent parenchyma and draining veins from the prescription isodose volume (PIV). 30,31 A small number of patients (,10) in our early practice underwent embolization to reduce the nidus volume in preparation for SRS; no patient after 1995 underwent planned embolization before SRS. Dose planning was performed using KULA (Elekta Instruments) from January 1990 until April 1993.…”
Section: Radiosurgery Techniquementioning
confidence: 99%
“…From the beginning of our AVM practice, dose planning was based on a combination of stereotactic biplanar angiography and either contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) to more effectively exclude the adjacent parenchyma and draining veins from the prescription isodose volume (PIV). 30,31 A small number of patients (,10) in our early practice underwent embolization to reduce the nidus volume in preparation for SRS; no patient after 1995 underwent planned embolization before SRS. Dose planning was performed using KULA (Elekta Instruments) from January 1990 until April 1993.…”
Section: Radiosurgery Techniquementioning
confidence: 99%
“…13,45 Nevertheless, biplanar stereotactic angiography alone is inade- quate for 3D reconstruction of an AVM shape. 8,14,27,28,34,46,47 This flaw is partially overcome by using 1 of 3 options: 1) the combination of stereotactic angiography and stereotactic CT (and/or MR imaging); 8,20,27,28,30,46 2) CT angiography; 4 or 3) MR angiography. 6,27 Despite general agreement that 3D imaging is essential for treating AVMs, the evidence that treatment plans based on CT or MR angiography are superior to those obtained with a combination of stereotactic angiography and contrast-enhanced CT is still lacking.…”
Section: Image Registrationmentioning
confidence: 99%
“…Neuroimaging, including CT and MRI, provides good anatomic resolution, but cannot discriminate the AVM nidus from the feeding arteries and draining veins [14]. On the other hand, conventional angiography provides orthogonal 2-dimensional projections of the AVM that dose outline the nidus margins and geometry; however, spatial information is lost because the dimensional reduction represents a source of inaccuracy in nidus definition, particularly in patients with irregularly shaped AVMs [14,15,16,17]. It has been suggested that AVM definition using images from multiple modalities for treatment planning is important and should be used as a routine tool for target delineation [18].…”
Section: Discussionmentioning
confidence: 99%